Rapid Metabolic Recovery of Donor Circulatory Death Liver Graft Using Whole Blood Perfusion: A Pig Study. Issue 7 (10th June 2021) - Yoshimoto, Syuhei; Ohara, Masayuki; Torai, Shinji; Kasamatsu, Hiroo; Ishikawa, Jun; Kimura, Takahiro; Nadahara, Soichi; Kobayashi, Eiji
Abstract : Background: Ex vivo perfusion technology has been actively developed to solve the problem of severe donor shortage. In this study, the ex vivo metabolic characteristics of porcine donation after circulatory death (DCD) liver in short-term perfusion using whole or diluted blood were compared with those of the in vivo transplanted state to evaluate their initial response to resuscitation. Methods: The porcine DCD model was constructed by clamping the thoracic aorta. After 60 min of blood flow cessation, retrieved livers were flushed with 500 mL of heparin saline (20 000 IU/L) followed by perfusion with 500 mL of cold histidine-tryptophan-ketoglutarate solution. The liver grafts were immersed in cold histidine-tryptophan-ketoglutarate solution for 60 min. Subsequently, normothermic ex vivo perfusion was performed with 20 000 IU/L of heparin added to the collected blood (whole blood group) or medium mixed with 10% whole blood (dilution group) for 3 h. Blood from the portal vein, the hepatic artery, and infra hepatica inferior vena cava was collected hourly and metabolomic analyses were performed. The other liver graft was heterotopically transplanted as a control (in vivo group). Each experiment was conducted once. Results: The guanosine levels demonstrated similar fluctuating trends in the whole blood and in vivo groups. In contrast, the levels increased during the perfusion in the diluted blood group. Fluctuations in choline metabolism demonstrated similar trends in the whole blood and in vivo groups. Conclusions: Ex vivo machine perfusion with whole blood over a short time resulted in a metabolic trend similar to that in the in vivo model. Further studies in this regard are warranted to progress in the utilization of DCD organs.